Molecular determinants in Frizzled, Reck, and Wnt7a for ligand-specific signaling in neurovascular development - Cho, Chris; Wang, Yanshu; Smallwood, Philip M; Williams, John; Nathans, Jeremy (eLife, 2019)
The molecular basis of Wnt-Frizzled specificity is a central question in developmental biology. Reck, a multi-domain and multi-functional glycosylphosphatidylinositol-anchored protein, specifically enhances beta-catenin signaling by Wnt7a and Wnt7b in cooperation with the 7-transmembrane protein Gpr124. Among amino acids that distinguish Wnt7a and Wnt7b from other Wnts, two clusters are essential for signaling in a Reck- and Gpr124-dependent manner. Both clusters are far from the site of Frizzled binding: one resides at the amino terminus and the second resides in a protruding loop. Within Reck, the fourth of five tandem repeats of an unusual domain with six-cysteines (the CC domain) is essential for Wnt7a stimulation: substitutions P256A and W261A in CC4 eliminate this activity without changing protein abundance or surface localization. Mouse embryos carrying ReckP256A,W261A have severe defects in forebrain angiogenesis, providing the strongest evidence to date that Reck promotes CNS angiogenesis by specifically stimulating Wnt7a and Wnt7b signaling.
Keywords: canonical Wnt signaling; Gpr124; Reck; Wnt7; blood-brain barrier; CNS angiogenesis